Altemeier procedure for incarcerated rectal prolapse in young age: a rare case report - Soni, Raj C.; Parmar, Kirit D.; Parikh, Sameer; Khatri, Urvish Kumar (International Surgery Journal, 2024)
Rectal prolapse is complete protrusion of rectum (procidentia) through anal canal. It is most commonly occurring in elderly age but rarely can occur in young age. Incarceration rarely complicates the chronically progressive form of full thickness rectal prolapse. We report the case of 38-year-old men who underwent emergency surgery for incarcerated rectal prolapse. Emergency perineal rectosigmoidectomy (altemeier procedure) was performed with diverting loop sigmoid colostomy. The successful treatment of this patient illustrates the value of altemeier procedure in difficult case of bowel incarceration.